Possible mechanisms of chronic leprosy-related arthritis - Cossermelli-Messina, Waldenise; Cossermelli, Wilson (São Paulo Medical Journal, 1997)
Microbial agents induce arthritis through mechanisms such as direct infiltration of tissue and by inducing autoimmune phenomena. The mechanisms involved in this last type of arthritis have been investigated. In experimental models of adjuvant and reactive arthritis, the involvement of T cells and in some cases mycobacteria in the development of arthritis have been confirmed. Cross-reactivity between the 65 kD mycobacterial protein and cartilage proteoglycans has been postulated as a possible mechanism. In this study, chronic peripheral arthritis was observed in patients with Hansen's disease, in patients with resolved Hansen's and in those with paucibacillary forms. This arthritis was not related to reactional states (erythema nodosum Ieprosum and reversal reaction), in contrast to several reports in the literature. The mechanisms by which microbes could induce chronic arthritis are discussed herein.